2022
DOI: 10.3892/etm.2022.11133
|View full text |Cite
|
Sign up to set email alerts
|

Low‑field magnetic stimulation improved cuprizone‑induced depression‑like symptoms and demyelination in female mice

Abstract: Depression is a common and disabling comorbidity of multiple sclerosis (MS), with currently no clear guidelines for treatment. Low-field magnetic stimulation (LFMS), a novel non-invasive neuromodulation intervention, has been previously demonstrated to rapidly alleviate mood disorders. The aim of the present study was to investigate the effects of LFMS on depression-like behaviors and demyelination in a well-established mouse model of MS. C57BL/6 female mice were fed a 0.2% cuprizone (CPZ) diet for 3 or 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…A spontaneous alternation was defined as any combination of three sequential entries in which the animal entered all three arms (e.g., ABC, CAB, or BCA, but not ABB). The percentage of spontaneous alternation was used as an index of working memory and calculated according to the following equation: The spontaneous alternation (%)=[(number of alternations)/(total arm entries-2)] x100( 32 ). After each session, the maze was cleaned with 70% ethanol to avoid odors.…”
Section: Methodsmentioning
confidence: 99%
“…A spontaneous alternation was defined as any combination of three sequential entries in which the animal entered all three arms (e.g., ABC, CAB, or BCA, but not ABB). The percentage of spontaneous alternation was used as an index of working memory and calculated according to the following equation: The spontaneous alternation (%)=[(number of alternations)/(total arm entries-2)] x100( 32 ). After each session, the maze was cleaned with 70% ethanol to avoid odors.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that low intensity rTMS in an intermittent theta burst stimulation pattern upregulated oligodendrocytes survival and promoted myelination. Four weeks of daily rTMS has been demonstrated to enhance oligodendrocyte myelination in both healthy adult mice and demyelinated mice, while also reducing depression-like symptoms and facilitating cognitive recovery in demyelinated mice ( Cullen et al, 2019 ; Wang et al, 2021 ; Mooshekhian et al, 2022 ). Recently, a randomized controlled trial has been conducted to assess the safety and remyelination in multiple sclerosis patients ( Makowiecki et al, 2022 ).…”
Section: Translational Approaches and Drugsmentioning
confidence: 99%
“…Evidence suggests that controlling neuronal excitability may be an appropriate novel intervention for clinical therapy of demyelination conditions. Neuronal activity can be stimulated directly or indirectly by various methods such as optogenetics, chemogenetics, transcranial stimulation, and sensory stimulation ( Nagy et al, 2017 ; Maas and Angulo, 2021 ; Mooshekhian et al, 2022 ). In this review, we focus on recent advances in neuronal activity and remyelination, as well as the related mechanisms of neural signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Depression, which may begin before the clinical diagnosis of MS, can significantly affect the patient's quality of life (3). Studies indicate that demyelination in the inner prefrontal cortex (PFC) and diffuse white matter (WM), such as the corpus callosum (CC), is associated with increased depressive-like behaviors (4,5). Additionally, the activation of neuroinflammatory agents and the increase of free radicals, such as nitric oxide (NO), which in turn induces further inflammatory responses, occur in patients with depression (6).…”
Section: Introductionmentioning
confidence: 99%